2019
DOI: 10.3855/jidc.10574
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, behaviour of the future healthcare professionals towards the self-medication practice with antibiotics

Abstract: Introduction: Self-medication with antibiotics (SMA) is a major health problem in the developing world including the kingdom of Saudi Arabia (KSA). This practice remains an emerging challenge for the healthcare providers. A few previous studies have estimated the prevalence of SMA among the general population of KSA, but there had been no such studies on healthcare students. We aimed to estimate the prevalence of SMA among medical, non-medical students and to evaluate its determinants. Methodology:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In our study, we found that 45.5% of respondents used self-medication for a variety of causes, but in a study by Banerjee I et al, 9 57.05% of respondents used self-medication. In our study, it was discovered that 47% of males and 54% of females selfmedicated, compared to 46.13% of females and 32.5% of males in a study by Kumar N et al 7 A study by Benameur T et al 10 found that 222 (94.5%) respondents were graduates, of whom 125 (56.8%) practiced self-medication. In the current study, the majority of respondents 115 (57.5%) were graduates.…”
Section: Discussionmentioning
confidence: 46%
“…In our study, we found that 45.5% of respondents used self-medication for a variety of causes, but in a study by Banerjee I et al, 9 57.05% of respondents used self-medication. In our study, it was discovered that 47% of males and 54% of females selfmedicated, compared to 46.13% of females and 32.5% of males in a study by Kumar N et al 7 A study by Benameur T et al 10 found that 222 (94.5%) respondents were graduates, of whom 125 (56.8%) practiced self-medication. In the current study, the majority of respondents 115 (57.5%) were graduates.…”
Section: Discussionmentioning
confidence: 46%
“…This was similar to the study of who reported negative attitude and inappropriate practice among health science students. [ 19 ] Most of the participants 52.5% in this survey didn't practiced SM. This result can be compared with the other findings where same or higher use of self-medication was reported.…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable with the results of some previous studies. For example, a recent study performed in Saudi Arabia among future prescribers showed that sore throat was the most common reported symptom, followed by fever and cough [ 47 ]. In addition, studies conducted in Nepal, India, Sri Lanka and China all showed that the common cold was the most common medical condition for which medical students self-medicated with antibiotics [ 18 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%